A numerical study of the suitability of rigid inclusion ground reinforcement beneath caisson quay walls - Holmwood, Andrew Graham (Department of Civil Engineering, 2017)
The objective of this study was to determine whether rigid inclusions are suitable for reinforcement of the foundation of a caisson quay wall functioning as a container terminal. Apart from their brittle behaviour under lateral loading, rigid inclusions are well suited to the large uniform loads and stringent post-construction deflection tolerances associated with container terminal structures. Their inherent strength and stiffness means they have certain advantages over other stiffening columns commonly used for ground reinforcement in port expansion projects. Their mechanical properties allow construction to unrestricted heights at any construction rate and, in theory, RIs can be applied to all soil types. Additionally the locations of many ports coincide with rivers, deltas and estuaries which are associated with poor soil conditions often requiring ground improvement. Their suitability is of practical significance to port planners and engineers who are faced with the challenge of providing satisfactory foundation performance that is cost effective. The addition of RI ground reinforcement for this structural application would allow for greater flexibility in meeting these challenges. The literature review for this study was broad in its scope with emphasis placed on describing the mechanics of the problem, analysis methods and suitable installation methods for execution in the marine environment. One of the key outcomes of the literature review was identifying the problem of lateral loading due to "free-field" lateral ground movements. In light of this, suitable strategies for limiting and accommodating lateral loading of the RIs were proposed. A numerical study of the proposed ground improvement scheme was undertaken using the 3D finite element method. The key model outputs were caisson deflections and RI forces, moments and stresses, for the various simulated construction phases up to operational conditions. The model results were assessed in terms of the key foundation performance criteria which were related to STS crane rail tolerances and limiting tensile stresses in the RIs. This study found that for a firm clay subsoil condition the proposed RI ground reinforcement scheme met the foundation performance criteria for this structural application provided (i) strategies to limit lateral loading were implemented and (ii) the RIs were reinforced over the length where they were not fully compressed. While this study provided insights into the behaviour of RIs for this structural application, ultimately suitability is a function of range of factors, in addition to the limited technical performance criteria derived for this study.